Factor structure of morphological and motor characteristics of a young table tennis players - Nikolic, I.; Furjan Mandic, G.; Kondric, M. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
The aim of this study was to determine the latent structure of morphological characteristics and motor abilities of young table tennis players (N=101) aged 9-11 years. This entailed 15 standard anthropometric measures being used to assess four latent morphological dimensions: longitudinal dimensionality, transversal dimensionality of the body, volume and body mass as well as subcutaneous adipose tissue. The selected measurements evenly reflect the International Biological Programme`s existing model of the morphological space. To evaluate motor abilities, 24 tests were used which best define latent dimensions: coordination, agility, frequency of movement, flexibility, explosive strength, speed, repetitive strength and endurance. Factor analysis was applied according to the method of principal components, the selection of eigenvalues by the Kaiser criterion and an orthogonal (varimax) rotation matrix of factor loadings. The obtained results indicate that in the morphological space of young table tennis players two factors were extracted: factor of skeletal dimensionality and adipose body volume factor. In the motor space, six factors were isolated: agility factor, explosive strength and frequency of movement factor, factor of the whole body coordination, factor of the shoulder and hip flexibility, repetitive strength factor and flexibility of the lower extremities factor. The obtained results will enable trainers to more objectively direct the long-term development of young players, especially for developing specific motor abilities in sensitive phases.